PENGARUH FAKTOR-FAKTOR FUNDAMENTAL TERHADAP HARGA SAHAM PT UNILEVER INDONESIA Tbk TAHUN 2004-2013 - Christera Kuswahyu Indira; Rini Dwiastutiningsih (Jurnal Ilmiah Ekonomi Bisnis, 2015)
The stock price reflects the value of a company. If the company achieve good performance, the company's stock will be much in demand by investors. Achieved a good performance can be seen in the company's financial statements published by the company (issuer).The purpose of this study was to determine the influence of fundamental factors to the stock price of PT Unilever Indonesia Tbk period 2004-2013. The method used is multiple linear regression analysis. Hypothesis testing using t-test and F test results showed that the partial net profit margin and return on equity does not affect the price of the shares of PT Unilever Indonesia Tbk only earning per share which affect the stock price of PT Unilever Indonesia Tbk. Simultaneously, net profit margin, return on equity, and earnings per share effect on the stock price of PT Unilever Indonesia Tbk. The data obtained by the author in the form of secondary data to obtain these data the authors made a visit to the website of PT Unilever Indonesia Tbk, the authors use the data overview of the financial period 2004 to 2013 were analyzed using SPSS. Keywords: net profit margin, return on equity, earnings per share, the stock price